Frontiers in cardiovascular biology: London 2012 – a scientific 'olympiad'. (September 2012) - Harding, Sian E
Imperial College London (UK) was the showcase for the second in the 'Frontiers in Cardiovascular Biology' series, a biennial meeting of the European Society of Cardiology Council on basic cardiovascular sciences, held from 30 March to 1 April 2012. The aim of this series is to bring researchers together to learn the very latest findings in cardiac and vascular sciences, and to see state-of-the-art and developing technologies that could impact cardiovascular research. Five keynote lectures, 25 scientific symposia and two translational lunchtime symposia were grouped around the central themes of bioimaging, degeneration and regeneration, and inflammation.